2020
DOI: 10.21203/rs.3.rs-47464/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Role of IL-22 in Persistent Allergic Airway Diseases Caused by House Dust Mite: A Pilot Study

Abstract: Background. Persistent allergic airway diseases cause a great burden worldwide. Their pathogenesis is not clear enough. There is evidence that one of the recently described cytokine interleukin (IL) 22 may be involved in the pathogenesis of these diseases. Scientists argue if this cytokine acts as proinflammatory or anti-inflammatory agent. The aim of this study was to investigate IL-22 level in patients with persistent allergic airway diseases caused by house dust mite (HDM) in comparison with healthy individ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Bayrak Degirmenci did not find a link between IL-22 and disease severity (17). The study which investigated IL-22 level in allergic airway diseases (allergic rhinitis with or without asthma) revealed a tendency that IL-22 level in serum and nasal lavage was increased in patients with allergic airway diseases caused by house dust mite and positively correlated with IL-10 level in serum and nasal lavage (19). Moreover, IL-22 level in nasal lavage negatively correlated with eosinophil count in a nasal smear in patients with allergic rhinitis and allergic asthma.…”
Section: Th22 and Il-22 In Allergic Rhinitis And Allergic Asthmamentioning
confidence: 94%
See 2 more Smart Citations
“…Bayrak Degirmenci did not find a link between IL-22 and disease severity (17). The study which investigated IL-22 level in allergic airway diseases (allergic rhinitis with or without asthma) revealed a tendency that IL-22 level in serum and nasal lavage was increased in patients with allergic airway diseases caused by house dust mite and positively correlated with IL-10 level in serum and nasal lavage (19). Moreover, IL-22 level in nasal lavage negatively correlated with eosinophil count in a nasal smear in patients with allergic rhinitis and allergic asthma.…”
Section: Th22 and Il-22 In Allergic Rhinitis And Allergic Asthmamentioning
confidence: 94%
“…Moreover, IL-22 level in nasal lavage negatively correlated with eosinophil count in a nasal smear in patients with allergic rhinitis and allergic asthma. A negative link was found between serum IL-22 and (Rhinoconjunctivitis Quality of Life Questionnaire) RQLQ in patients with allergic airway diseases (19). A systematic review analysing six clinical studies which investigated IL-22 level in patients with allergic airway diseases showed that IL-22 level and IL-22 gene expression in serum, plasma and nasal mucosa was higher in children and adults with allergic airway diseases than in healthy individuals (20).…”
Section: Th22 and Il-22 In Allergic Rhinitis And Allergic Asthmamentioning
confidence: 99%
See 1 more Smart Citation